Timing and Duration of Exposure in Evaluations of Social Programs - King, Elizabeth M. (World Bank, 2012)
Impact evaluations aim to measure the outcomes that can be attributed to a specific policy or intervention. While there have been excellent reviews of the different methods for estimating impact, insufficient attention has been paid to questions related to timing: How long after a program has begun should it be evaluated? For how long should treatment groups be exposed to a program before they benefit from it? Are there time patterns in a program's impact? This paper examines the evaluation issues related to timing, and discusses the sources of variation in the duration of exposure within programs and their implications for impact estimates. It reviews the evidence from careful evaluations of programs (with a focus on developing countries) on the ways that duration affects impacts.